2014
DOI: 10.1177/000313481408001225
|View full text |Cite
|
Sign up to set email alerts
|

Single-center Experience with Live Kidney Donors 60 Years of Age or Older

Abstract: Live donor kidney transplantation (LDKT) with elderly donors is a controversial topic. The purpose of this study was to evaluate donor and recipient outcomes involving live donors 60 years of age or older. All LDKTs performed at our institution from January 2000 to January 2011 were evaluated. Statistical analysis included t test, uni- and multivariate regression analyses, and Kaplan-Meier survival analysis. Forty-seven LDKTs were performed with donors 60 years of age or older. Median donor age was 65 years. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…A Japanese study showed that donor age had no influence on the deterioration of renal function after nephrectomy, despite that elderly were significantly more often affected by hypertension [31]. Other factors that may adversely affect renal function are female gender and obesity [32,33]. Multivariate analysis showed that donation of the better functioning kidney did Multiple demographic and health characteristics are used together to estimate the projected long-term risk of ESRD among living kidney donor candidates [5].…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study showed that donor age had no influence on the deterioration of renal function after nephrectomy, despite that elderly were significantly more often affected by hypertension [31]. Other factors that may adversely affect renal function are female gender and obesity [32,33]. Multivariate analysis showed that donation of the better functioning kidney did Multiple demographic and health characteristics are used together to estimate the projected long-term risk of ESRD among living kidney donor candidates [5].…”
Section: Discussionmentioning
confidence: 99%
“…Para receptores de injertos de donadores > 60 años, la supervivencia a cinco años está entre 80-100% y la supervivencia del injerto censurada para muerte entre 95-100%, resultados que fueron similares si el injerto provenía de un donador joven. [13][14][15][16] EDAD DEL RECEPTOR Queda claro que la esperanza de vida se ha incrementado y por ende el número de pacientes adultos mayores con enfermedad renal crónica terminal (ERCT). Todo paciente con ERCT es candidato a ser evaluado para el protocolo de trasplante renal, sin importar la edad.…”
Section: Edad Del Donadorunclassified